2003
DOI: 10.1152/ajpgi.00164.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginger on motion sickness and gastric slow-wave dysrhythmias induced by circular vection

Abstract: Ginger has long been used as an alternative medication to prevent motion sickness. The mechanism of its action, however, is unknown. We hypothesize that ginger ameliorates the nausea associated with motion sickness by preventing the development of gastric dysrhythmias and the elevation of plasma vasopressin. Thirteen volunteers with a history of motion sickness underwent circular vection, during which nausea (scored 0-3, i.e., none to severe), electrogastrographic recordings, and plasma vasopressin levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
135
4
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 27 publications
(35 reference statements)
6
135
4
1
Order By: Relevance
“…Furthermore, ginger reverses cisplatin-induced delays in gastric emptying in animal models (Sharma and Gupta, 1998). In a model of experimental motion sickness, gastric slow wave rhythm disturbances evoked by circular vection were prevented by treatment with ginger root (Lien et al, 2003). The effects of ginger on prostaglandin pathways as inducers of gastric dysrhythmic activity are unknown; however, it exhibits inhibitory effects on prostaglandin and leukotriene synthesis in other models, including platelets and RBL-1 cell lines (Srivastava, 1984;Kiuchi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, ginger reverses cisplatin-induced delays in gastric emptying in animal models (Sharma and Gupta, 1998). In a model of experimental motion sickness, gastric slow wave rhythm disturbances evoked by circular vection were prevented by treatment with ginger root (Lien et al, 2003). The effects of ginger on prostaglandin pathways as inducers of gastric dysrhythmic activity are unknown; however, it exhibits inhibitory effects on prostaglandin and leukotriene synthesis in other models, including platelets and RBL-1 cell lines (Srivastava, 1984;Kiuchi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibiting cyclooxygenase and lipoxygenase activity, ginger exhibits effects on 5-HT 3 -mediated functions (Huang et al, 1991;Shibata et al, 1999). In experimental motion sickness in healthy humans, ginger blunts the increase in plasma vasopressin levels in response to circular vection, indicating possible actions on the release of this transmitter (Lien et al, 2003). Finally, loss of nitric oxide function has been proposed as a cause of impaired gastric motor function in rodent models of diabetic gastroparesis (Watkins et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism was supported by the results of a randomized, double-blind trial which demonstrated the ability of the ginger to accelerate gastric emptying and stimulated antral contractions 24 . Some asserted that the antiemetic effect results from the inhibition of serotonin receptors in the gastrointestinal system and the central nervous system 'vomiting center' , as well as the inhibition of vasopressin which causes a reduction in tachygastric activity [25][26][27][28][29] . There are various active ingredients found in the ginger including gingerol, shogaol, and galanolactone, which produce antiemetic effects using difference mechanisms [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…The rhizomes of ginger have been used for medicinal purposes in traditional Ayurvedic medicines to treat dyspepsia, asthma, cough, diarrhea, cardiac disorders, nausea, vomiting and inflammation (107)(108)(109). Ginger, or its extracts, contains limonene, cymene, cineole, zingiberene, terpenoid, geraniol, shogaol and gingerol, among other constituents, which demonstrate diverse pharmacological properties including analgesic, anti-inflammatory, antitumor and antioxidant activities (110)(111)(112). Previous studies have attested to the radioprotective potential of ginger (113,114).…”
Section: Zingiber Officinalementioning
confidence: 99%